Acronyms and abbreviations in library and information work : a reference handbook of British usage - Montgomery, A.C., comp. and ed. (The Library Association LondonGB, 1982)
Provides a quick reference listing of acronyms and abbreviations encountered in the general English language literature of librarianship and information work. Primarily covers projects, organizations, associations, information resources and services, and technical terms, abstracting, indexing and professional services and journals. Selectively includes other fields such as archives, museums, translation, and computer technology.